PENINGKATAN KUALITAS SUMBER DAYA MANUSIA MELALUI PERAN KEPEMIMPINAN KEPALA SEKOLAH - Muhammad Abrori; Chusnul Muali (JUMPA : Jurnal Manajemen Pendidikan, 2020)
The purpose of writing this article is to find out the role of the principal's leadership in improving the quality of human resources in the school. The problem of human resources in various schools is that the quality is not optimal and evenly distributed. The method and type of data collection in this research is library research by collecting books, journals and the results of previous studies that support research themes, including literature on leadership which includes the role of the principal's leadership, quality improvement, and human resources at school. The results of this study indicate that the leadership variable is the most important and urgent variable in the effort to create or realize quality education.